PRECAMBRIAN GEOBIOLOGY - Rozanov A.Yu. (My University, 2006)
The appearance of Bacteria sensu lato, Eukaryota, Metaphyta, Metazoa, etc., along with the oxygenization of the atmosphere, are shown to have occurred much earlier than was previously assumed. Paleontological data clearly indicate that the difference between surface temperature of the Earth in the Archaen and now was no more than 30°C.